Synthesis and Charcterization of Oxoyanadium(IV) Coordination Compounds Derived from 4[N-(4-Hydroxy-3-Methyl Benzalidene) Amino] Antipyrine Semicarbazone and 4[N-(3,4,5-Trimethoxybenzalidene) Amino] Antipyrine Semicarbazone† - singh, Lakshman; Upma Singh, Ms. (Asian Journal of Chemistry, 2010)
The interaction of various VO2+ salts in non-aqueous medium with 4[N-(4-hydroxy-3-methoxy benzalidene) amino] antipyrine semicarbazone (HMBAAPS) and 4[N-(3,4,5-trimethoxybenzali.· dene) amino] antipyrine sernicarbazone (TMBAAPS) results in the formation of the complexes of the general composition VOX2·L (X = Cl-, Br-, I-, NO3- or NCS-) and VO(ClO4)2·L·H2O (L = HMBAAPS or TMBAAPS). The ligands behave as tridentate (N, N, O) donors in these complexes. All the complexes are pentacoordinated. Thermal stabilities of the complexes have been studied through thermogravimetric analysis.